2015
DOI: 10.5152/jtgga.2015.15038
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of three-dimensional multislice view Doppler in diagnosis of morbid adherent placenta

Abstract: Placenta accreta occurs when placental trophoblasts invade the endometrium beyond the Nitabuch's layer of decidua basalis, placenta increta occurs when placental trophoblasts invade the myometrium, and placenta percreta occurs when placental trophoblasts invade the serosa (1, 2). Morbid adherent placenta (MAP) is generally associated with excess blood loss, bladder injuries and hysterectomies (3, 4). The incidence of MAP has increased significantly over the last 50 years (5, 6). A past history of a cesarean de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…This suggested that if the retroplacental sonolucent area between the placenta and the uterus was preserved, morbidly adherent placenta was unlikely to occur with high NPV of 82%, 82.8% respectively.The current work showed that the presence of focal exophytic masses invading the urinary bladder had the highest PPV of 100%. This was in agreement with Moniem et al, 2015[16] but againstShih et al, 2009 [17] and Pilloni et al,2016 [18] studies which showed that thinning or disruption of hyperechoic serosa-bladder interface had the highest PPV of 100% and 77.8% respectively while irregular retroplacental sonolucent zone had the highest NPV of 82.8% and this was in accordance with Pilloni et al, 2016[18], but against Shih et al, 2009[17] and Moniem et al,2015…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This suggested that if the retroplacental sonolucent area between the placenta and the uterus was preserved, morbidly adherent placenta was unlikely to occur with high NPV of 82%, 82.8% respectively.The current work showed that the presence of focal exophytic masses invading the urinary bladder had the highest PPV of 100%. This was in agreement with Moniem et al, 2015[16] but againstShih et al, 2009 [17] and Pilloni et al,2016 [18] studies which showed that thinning or disruption of hyperechoic serosa-bladder interface had the highest PPV of 100% and 77.8% respectively while irregular retroplacental sonolucent zone had the highest NPV of 82.8% and this was in accordance with Pilloni et al, 2016[18], but against Shih et al, 2009[17] and Moniem et al,2015…”
supporting
confidence: 88%
“…In the present study, for 2D-US, loss of retroplacental sonolucent zone has the [16] whose study showed that disruption of serosa-bladder interface had the highest NPV of 73% and 84.1% respectively.…”
Section: Discussionsupporting
confidence: 49%
“…In Abdel Moniem et al [25] study on 50 pregnant patients with suspected MAP, using both 2D US and 3D Power Doppler scans to assess the best parameter that could predict MAP prenatally. The results show that the best 2D parameter was disruption of uterine serosal interface (81.8 sensitivity), so could be used in screening for MAP and the best parameter for confirmation of MAP diagnosis was presence of exophytic mass invading the bladder with 94.9% specificity.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Ultrasound is the most commonly used tool in the prenatal diagnosis of placental abnormalities, 13 and chorioangioma as well. Hypoechoic, well-circumscribed, ovoid or round intraplacental mass different from the rest of placenta containing small anechoic spaces that protruded into the amniotic cavity are the usual gray scale findings.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%